Maternal and infant Bordetella pertussis infection - Narkevičiūtė, Irena; Kavaliūnaitė, Ema; Janušaitienė, Rūta (Acta medica Lituanica, 2014)
Background. Pertussis continues to be a public health concern around the world because of increasing morbidity among vaccinated children and adults, severe disease forms in infants and late diagnosis. It is frequently believed that pertussis is exclusively a “childhood disease”, but there have been increasing reports of B. pertussis infection among adolescents and adults, although the peak incidence and the highest mortality occur among infants. Case presentation. 7-week-old infant illness started with a dry cough, on the 8th day of her illness it became paroxysmal. The infant’s recurrent apnea episodes started on the day 12 of the illness, she started vomiting and developed severe respiratory failure. The patient required intubation and ventilation and stayed in PICU for 9 days. Blood showed lymphocytic leukocytosis. Pertussis diagnosis was confirmed by specific IgM antibody seroconversion. Disease to her 30-year-old mother began with catarrhal symptoms, later her paroxysmal coughing became accompanied by vomiting. Atypical bacterial bronchitis was suspected. Rigorous epidemiological history and detection of pertussis antibodies have helped to the confirmation of the pertussis diagnosis. The clinical course of B. pertussis infection in the infant was severe, and the mother’s course was mild. Conclusions. Our presented clinical case of the infant and her mother’s B. pertussis infection illustrates the complex diagnostic difficulties in diagnosing pertussis, requiring laboratory confirmation, analysis of epidemiological data and appropriate evaluation. Pertussis to the infant and the mother occurred with the typical three stages: catarrhal, paroxysmal and convalescente. The infant underwent a severe form of the disease, but the outcome was good. Understanding the source of pertussis may provide new approaches to preventing pertussis in the most vulnerable infants.